1969
DOI: 10.1088/0022-3727/2/6/313
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from metal particles in a vacuum gap

Abstract: The motion of a charged metal particle which is itself a source of field emission has been investigated. It will be shown that the effect of electron emission from a particle may significantly affect its behaviour and may even reverse its direction of motion in the electric field within a vacuum gap. Cathode-directed particles have their energies increased by this process, while the reverse is true for anode-directed particles. These findings are in accord with the results of other investigators who have sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Hence the MP starts to move in the interelectrode space, under vacuum, towards the cathode, driven by the macroscopic electric field. Its initial charge Q MP [47] is controlled by the electrode surface electric field. This charge is expressed as follows:…”
Section: Microparticle Modelmentioning
confidence: 99%
“…Hence the MP starts to move in the interelectrode space, under vacuum, towards the cathode, driven by the macroscopic electric field. Its initial charge Q MP [47] is controlled by the electrode surface electric field. This charge is expressed as follows:…”
Section: Microparticle Modelmentioning
confidence: 99%
“…U c is the critical voltage determined by the complemented Cranberg's hypothesis (7). U b is the instant breakdown voltage.…”
Section: Cranberg's Hypothesis Applied To An Impulse Voltage Breakdowmentioning
confidence: 99%
“…As a result, there have been a number of theories concerning the processes involved when a breakdown of a vacuum gap occurs [1][2][3][4][5][6][7][8][9][10]. Researches on vacuum breakdown have shown that breakdown tended to be field-dependent for a short contact gap d ≤0.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Charge may in principle be exchanged between the particle and target either by direct ohmic conduction through the surface films during conthct, or by close-proximity quantum mechanical tunnelling. In the special case where both surfaces are atomically clean, charge exchange would only be limited by the electrical properties of the interacting materials, and would be completed in a time comparable with the relaxation time T of typical metals, where T N 10-19-10-17 s. Since 7 < f C , it follows that the reversed charge acquired by a particle under these circumstances would be the equilibrium value for a sphere in contact with a plane (Hurley and Parnell 1969), which for a vacuum-metal interface would be…”
Section: 2 Electrical Considerationsmentioning
confidence: 99%
“…It is significant to note from these computations that E1 provides the dominant contribution for all values of g, so that Vp(g) z qI/ZCo(g) to a good approximation. It is also important to note from figure 5 that E g c 109 V m-1 for all conditions, so that the possibility of in-flight field emission from the target to the particle (Hurley and Parnell 1969) can be ignored in these experiments.…”
Section: 2 Electrical Considerationsmentioning
confidence: 99%